2002
DOI: 10.1007/bf02859372
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic modalities for Gastroesophageal Reflux

Abstract: Our results suggest that a combination of diagnostic modalities may be required to diagnose GER in young children. Ambulatory 24 hour pH monitoring appears to be the single best investigation and combining it with EB and/or GS can help to detect maximum number of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…(27) It should however be noted that for this population, although attempts have been made, no ‘true’ normative values have been established because of the ethics of performing invasive studies in healthy infants and children. (75, 95) The authors found the RI measured by pH-metry had a sensitivity and specificity 50% and 82%, respectively, using history and physical examination as the gold standard method for diagnosing GERD.…”
Section: Question 3: What Diagnostic Interventions Have Additional Vamentioning
confidence: 99%
See 1 more Smart Citation
“…(27) It should however be noted that for this population, although attempts have been made, no ‘true’ normative values have been established because of the ethics of performing invasive studies in healthy infants and children. (75, 95) The authors found the RI measured by pH-metry had a sensitivity and specificity 50% and 82%, respectively, using history and physical examination as the gold standard method for diagnosing GERD.…”
Section: Question 3: What Diagnostic Interventions Have Additional Vamentioning
confidence: 99%
“…The last and most recent study used the Reflux Index (RI, defined as the percentage of time that pH < 4) to determine pathological GERD (where abnormal was defined as pH < 4 for >10% for infants <1 year and 5% infants >1 year) (27). It should however be noted that for this population, although attempts have been made, no ''true'' normative values have been established because of the ethics of performing invasive studies in healthy infants and children (75,95). The authors found the RI measured by pH-metry had a sensitivity and specificity 50% and 82%, respectively, using history and physical examination as the gold standard method for diagnosing GERD.…”
Section: Ph-metry/wireless Ph Recordingmentioning
confidence: 99%
“…( 27) It should however be noted that for this population, although attempts have been made, no 'true' normative values have been established because of the ethics of performing invasive studies in healthy infants and children. (75,95) The authors found the RI measured by pH-metry had a sensitivity and specificity 50% and 82%, respectively, using history and physical examination as the gold standard method for diagnosing GERD.…”
Section: Ph-metry/wireless Ph Recordingmentioning
confidence: 99%
“…It also entails a relatively low radiation burden. According to most studies, the sensitivity of gastro-esophageal scintigraphy for detection of GER in comparison to pH monitoring ranges from 60% to 90% [4], specificity is over 90% [5] [6].…”
Section: Discussionmentioning
confidence: 99%